Lysosomes, Lysosomal Storage Diseases, and Inflammation - Simonaro,Calogera M. (2016)
Abstract Lysosomes were originally described in the early 1950s by de Duve who was also the first to recognize the importance of these organelles in human disease. We know now that lysosomes are involved in numerous biological processes, and abnormalities in lysosomal function may result in a broad range of diseases. This review will briefly discuss the role of lysosomes in inflammation and how disruption of normal lysosomal function in the lysosomal storage diseases (LSDs) leads to abnormalities in inflammation and immunity.